Pengaruh Service Quality Dan Price Terhadap Repurchase Intention Melalui Customer Satisfaction Pada Bengkel Honda AHASS Sukma Motor II (Studi Pada Pelanggan Mahasiswa Universitas Islam Malang) - Olive Ryan Wibowo; N. Rachma; Andi Normala (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The purpose of this study was to examine the effect of Service Quality, Price on Repurchase Intention through Customer Satisfaction at the Honda AHASS Sukma Motor II Workshop Malang (Study on customers of Malang Islamic University students). This type of research is explanatory research using a quantitative approach. The sampling technique used in this study is non-probability sampling with a purposive sampling approach. The data collection method in this study was carried out by distributing online questionnaires with a Likert scale given to respondents who had made repeat purchases at the Honda AHASS Sukma Motor II workshop. The sample used in this study were 75 respondents. Research data were analyzed using IBM SPSS Software. The results of this study found that service quality and price directly affect repurchase intention. Service quality and price have a direct effect on customer satisfaction. Repurchase intention has a direct effect on customer satisfaction. Service quality and price have a direct effect on customer satisfaction as an Intervening Variable. Keywords: service quality, price, repurchase intention, customer satisfaction